Ṭāhā ‘Abd al-Raḥmān’s Philosophical Contribution to Theorize Ethical Maqāṣid - Abid Rohmanu; Khusniati Rofiah (Al-Ahkam, 2023)
The ethical values of maqāṣid have been buried by the ḥarfiyyah-linguistic approach (ta’līlī-bayānī). The ethical paradigm of maqāṣid must be constructed to balance the ta’līlī-bayānī approach. This paper examines the philosophy of Ṭāhā ‘Abd al-Raḥmān in theorizing ethical maqāṣid. This paper focuses on two aspects. First, how does ‘Abd al-Raḥmān theorize the ethical maqāṣid? Second, how does ‘Abd al-Raḥmān conceptualize the relationship between Islamic law and ethics? This article is a literary research referring to some important books of ‘Abd al-Raḥmān. Using a moral philosophy approach, the writer concludes: first, ‘Abd al-Raḥmān’s ethical theorization of maqāṣid is a synthesis between ethics and uṣūl al-fiqh. This synthesis outlines the new pillars of maqāṣid. ‘Abd al-Raḥmān theoretically shifted legal reasoning from al-ta’līl al-sababī (attribute causality) to al-ta’līl al-ghā'i (maṣlaḥah causality). According to him, the only rationalization of Islamic law is maṣlaḥah, that is khuluq (ethics). Based on that premise, ‘Abd al-Raḥmān asserts that moderation is the accommodation of legal and ethical aspects of Islamic law. This paper recommends the importance of a moral philosophy approach to Islamic law. This approach is an effort to ground the maqāṣid in many legal cases loaded with morality.